Mekanisme Transaksi pada Sistem Informasi Akuntansi dan Penerapan pada Perbankan Syariah - Yulita Astri; M. Irwan Padli Nasution (MES Management Journal, 2023)
The purpose of this study was to determine the extent of the mechanism and application of the accounting information system in Islamic banking. This research uses the library method which is part of the qualitative method. In collecting data the researchers used a literature study where data sourced from previous researchers were then analyzed so as to answer the existing problems, for supporting data the researchers found from various other sources such as books and articles that were accurate. The results of this study indicate that the mechanism and application of accounting information systems in Islamic banking is in accordance with the relevant theory or in accordance with sharia principles. Nevertheless, Islamic banking is still expected to provide the latest innovations or changes to the accounting information system to support efficiency and effectiveness in the performance of Islamic banking. Keywords: Transaction Mechanism, Accounting Information System, Islamic Banking